Fatigue Management Principles and Practices for Improving Workplace Safety (Springer New York, 2018)
In this soon-to-be gold-standard text, a distinguished panel of experts provides a comprehensive discussion of the various medical, neurological, psychiatric, and psychological factors underlying fatigue and sleepiness in the workplace and in patients. In reviewing current best practices in managing fatigue and sleepiness conditions to improve workplace safety, the book importantly begins with an overview of fatigue's definitions and concepts. It then moves into discussing the historical perspective on sleepiness and fatigue, the definitions and classifications of fatigue, and assessments of fatigue in the laboratory and in clinical settings. The book continues by exploring medical causes of fatigue in detail; how medication and recreational agents may result in fatigue; and the treatment of sleep disorders. Additional topics include best practices in the treatment of narcolepsy and hypersomnia, a review of circadian rhythm and fatigue, the treatment of heart failure and improvement in fatigue, and the management of fatigue in hospitalized patients. A major contribution to the field, this invaluable title will be of significant interest to all clinicians concerned with safeguarding safety in the workplace by accurately diagnosing and managing patients with fatigue and sleepiness problems. Researchers will also find this title of great interest.